Influence of composition of Hg1−xCdxTe (x = 0.22–0.57) epitaxial film on dynamics of accumulation and spatial distribution of electrically active radiation defects after boron implantation. (17th April 2019) - Voitsekhovskii, A V; Grigoryev, D V; Korotaev, A G; Kokhanenko, A P; Lozovoy, K A; Izhnin, I I; Savytskyy, H V; Yu Bonchyk, O; Dvoretsky, S A; Mikhailov, N N; Varavin, V S; Yakushev, M V
Abstract: In this paper experimental results of research of boron ion implantation into Hg1− x Cd x Te epitaxial films of various compositions x are presented. Samples of epitaxial films were grown by the method of molecular beam epitaxy and irradiated by boron ions with the energy of 100 keV at room temperature in the range of irradiation doses 10 12 –10 15 ions cm −2 . As a result of the experimental investigations an evidence of influence of epitaxial film composition on the dynamics of accumulation and spatial distribution of electrically active radiation defects is obtained.